Evaluation of antimutagenic, antiangiogenic, and cytotoxicity against cancerous cells of mycelial extract of Cordyceps militaris - Deshmukh, Niketan; Lakshmi, Bhaskaran (Vietnam Journal of Biotechnology, 2025)
The high incidence and mortality rates of cancer necessitate the continuous search for effective anticancer therapies. Although synthetic drugs have been instrumental in modern medicine, their side effects drive the exploration of new, less harmful alternatives. Natural compounds are particularly favoured for their specificity, minimal side effects, and cost-effectiveness. In this study, the methanolic mycelial extract of Cordyceps militaris was evaluated for its antimutagenic, antiangiogenic, and cytotoxic properties. Antimutagenic activity assessed using the AMES test revealed a significant, concentration-dependent reduction in mutagenicity induced by sodium azide, benzo[a]pyrene, and 4-nitroquinoline-N-oxide in Salmonella tester strains TA98, TA100, and TA102, with up to 68.4% inhibition. Antiangiogenic effects, examined via the chorioallantoic membrane (CAM) assay, demonstrated substantial concentration-dependent inhibition of angiogenesis, achieving up to 88.4% inhibition at 100 µg/ml. The extract effectively suppressed the formation of angiogenic branch points, suggesting a potential role in inhibiting tumor neovascularization. Cytotoxic effects on the MDA-MB-231 breast cancer cell line, assessed through MTT assay, indicated a marked reduction in cell viability, with an IC₅₀ value of 54.86 µg/ml, while no significant cytotoxicity was observed in normal Vero cells. Morphological observations of treated cancer cells showed distinct cytoplasmic condensation, cell shrinkage, and detachment, indicative of apoptotic cell death. These findings highlight the multifaceted anticancer potential of C. militaris mycelial extract. This study underscores the therapeutic potential of C. militaris as a natural source of anticancer agents and provides a scientific foundation for further preclinical and clinical exploration.